2013
DOI: 10.1186/1472-6750-13-111
|View full text |Cite
|
Sign up to set email alerts
|

CdSe/ZnS Quantum Dots trigger DNA repair and antioxidant enzyme systems in Medicago sativacells in suspension culture

Abstract: BackgroundNanoparticles appear to be promising devices for application in the agriculture and food industries, but information regarding the response of plants to contact with nano-devices is scarce. Toxic effects may be imposed depending on the type and concentration of nanoparticle as well as time of exposure. A number of mechanisms may underlie the ability of nanoparticles to cause genotoxicity, besides the activation of ROS scavenging mechanisms. In a previous study, we showed that plant cells accumulate 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Additional work provided further information on the possible involvement of the Tdp1β gene in the plant stress response. Santos et al [ 5 ] showed the upregulation of Tdp1β gene in Medicago sativa suspension cultures exposed to genotoxic doses of CdSe/ZnS quantum dots, highlighting a strong correlation with DNA damage accumulation/repair kinetics. An RNA-Seq analysis carried out in MtTdp1α -depleted M. truncatula plants revealed that the MtTdp1β gene does not play a redundant function since the β isoform was not able to compensate for the lack of MtTdp1α gene in planta [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional work provided further information on the possible involvement of the Tdp1β gene in the plant stress response. Santos et al [ 5 ] showed the upregulation of Tdp1β gene in Medicago sativa suspension cultures exposed to genotoxic doses of CdSe/ZnS quantum dots, highlighting a strong correlation with DNA damage accumulation/repair kinetics. An RNA-Seq analysis carried out in MtTdp1α -depleted M. truncatula plants revealed that the MtTdp1β gene does not play a redundant function since the β isoform was not able to compensate for the lack of MtTdp1α gene in planta [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their increasing prevalence in the environment, the toxicity of quantum dots in plants is largely unknown. In a pioneer study, Santos et al ( 2013 ) used a battery of tests and gene expression related with DNA repair, and demonstrated that 10 nM 3-mercaptopropanoic coated-CdSe/ZnS quantum dots were cytotoxic and genotoxic to Medicago sativa cells. In this and other pioneer studies, the comet assay can play a pivotal role as a tool to assess environmental impacts of suspected emerging nanocontaminants.…”
Section: Nanocompoundsmentioning
confidence: 99%
“…Santos et al ( 2013 ) demonstrated in Medicago sativa that exposure to increasing concentrations of MPA-CdSe/ZnS quantum dots, led to an increase of DNA damages, and up-regulated the transcription of the DNA repair enzymes formamidopyrimidine DNA glycosylase, tyrosyl-DNA phosphodiesterase I and DNA topoisomerase I.…”
Section: Comet Assay and Putative Genetic Associationsmentioning
confidence: 99%
“…Metal sulphide nanomaterials have gained more attention in the field of cancer therapeutics due to their reactive oxygen species (ROS) generating and apoptosis inducing ability. [ 20–22 ] Compared with other metal sulphide nanoparticles, ZnS NPs have a higher surface‐to‐volume ratio, quantum size effect, quantum tunnelling effect, optical absorption, chemical activity, catalysis, and thermal resistance properties, therefore rendering them with various chemical, optical and biological applications like biosensors, drug delivery, photocatalysis, and theranostics. [ 23 ] Recently, ZnS NPs have been shown to induce cytotoxic effects in leukaemic and retinal pigment epithelial cells.…”
Section: Introductionmentioning
confidence: 99%